Pendapatan dan Laba Bersih Sebelum dan Sesudah Pendanaan di Financial Teghnology: Studi UMKM Kota Palembang - Nova Urba; Yuliani Yuliani; Rasyid HS Umrie (MBIA, 2019)
Industry 4.0 now brings up an innovation in all fields. One of them is the financial services sector by combining application-based lending technology. Innovations in trends in financial services related to access to financial products are known as Financial Technology (FinTech). This study aims to analyze the differences in income and net income before and after lending at FinTech. The research sample using the snow ball method was 26 respondents who had MSMEs. Data collection by questionnaire and data collected from 15 June to 15 July 2019. The method of data analysis is t-paired test. The research findings show that there are significant differences in MSME revenue after lending at FinTech. Net income has a significant difference after lending at FinTech. Research limitations for FinTech data in the Financial Services Authority or OJK are not yet complete, so the profile of MSMEs that conduct lending through FinTech is not yet in the database.